Continued treatment with nintedanib in patients with systemic sclerosis-associated interstitial lung disease: data from SENSCIS-ON. Issue 12 (16th August 2022) - Allanore, Yannick; Vonk, Madelon C; Distler, Oliver; Azuma, Arata; Mayes, Maureen D; Gahlemann, Martina; James, Alexandra; Kohlbrenner, Veronika; Alves, Margarida; Khanna, Dinesh; Highland, Kristin B
Abstract : Objectives: In the SENSCIS trial in patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD), nintedanib reduced the rate of decline in forced vital capacity (FVC) versus placebo, with adverse events that were manageable for most patients. An open-label extension trial, SENSCIS-ON, is assessing safety and FVC decline during longer term nintedanib treatment. Methods: Patients who completed the SENSCIS trial or a drug–drug interaction (DDI) study of nintedanib and oral contraceptive on treatment were eligible to enter SENSCIS-ON. Adverse events and changes in FVC over 52 weeks of SENSCIS-ON were assessed in patients who received nintedanib in SENSCIS and continued nintedanib in SENSCIS-ON ('continued nintedanib' group) and in patients who received placebo in SENSCIS and initiated nintedanib in SENSCIS-ON or who received nintedanib for ≤28 days in the DDI study ('initiated nintedanib' group). Results: There were 197 patients in the continued nintedanib group and 247 in the initiated nintedanib group. Diarrhoea was reported in 68.0% and 68.8% of patients in these groups, respectively. Adverse events led to discontinuation of nintedanib in 4.6% and 21.5% of the continued nintedanib and initiated nintedanib groups, respectively. Mean (SE) changes in FVC from baseline to week 52 of SENSCIS-ON were −58.3 (15.5) mL in the continued nintedanib group and −44.0 (16.2) mL in the initiated nintedanib group. Conclusions: The safety profile of nintedanib over 52 weeks of SENSCIS-ON was consistent with that reported in SENSCIS. The change in FVC over 52 weeks of SENSCIS-ON was similar to that observed in the nintedanib group of SENSCIS.